Determinants of Stock Prices on The Indonesian Stock Exchange (Study on Manufacturing Companies in The Automotive Industry Sector) - Wahyuni, A. Khadija; Badollahi, Ismail; Abdi, Muhammad Nur (SENTRALISASI, 2024)
Determinants of share prices listed on the Indonesian Stock Exchange (study of manufacturing companies in the automotive industry sector). This study finds a deep meaning regarding the essence that in simple terms share prices can be a reference for investors in making investment decisions and also reflect market expectations for the company. The aim of this research is to determine the influence of Capital Structure, capital adequacy, level of financing and profitability on share prices in manufacturing companies in the automotive industry sector listed on the Indonesia Stock Exchange (BEI). The total sample in this study was 12 companies in the Automotive Industry Sector taken from official website of the Indonesian Stock Exchange. The type of research used in this research is quantitative research using an explanatory research approach. The data processed is data taken from financial reports listed on the Indonesia Stock Exchange (BEI) from 2018-2022. The research results of the hypothesis which has a significant influence on share prices concluded that Capital structure and Profitability have a positive influence on share prices. Meanwhile, the variables capital adequacy and level of financing, based on research that has been carried out, can be concluded that they do not have a positive effect on share prices.